THE INTERNATIONAL DIMENSION OF PEACE EDUCATION IN THE PERSPECTIVE OF KNOWLEDGE DIPLOMACY DEVELOPMENT - Наталія Авшенюк (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2022)
The article is devoted to the study of the experience of peace education formation in the United Nations Universities on the basis of cultural and knowledge diplomacy. The important strategic aspects of knowledge diplomacy are defined: the diversity of participants and partners; recognition of different motives and needs, as well as collective use of resources of all participants; cooperation and partnership; availability and support of cooperation on different levels; building and strengthening relations between countries; search for common approaches to solving global problems of mankind, in particular the resolution of international conflicts through the development of peacebuilding. The article proposes an analysis of the basic concepts and theoretical provisions for Peace and Conflict Studies (PACS) as a combination of two academic disciplines: Peace Studies and Peace Education. On the basis of an integrated analysis of literary sources, the key aspects of its theoretical foundations, which have a common methodological basis, are outlined in the research. It was revealed that the «Peace Studies» examines the causes of wars, security phenomena and non-violence; methods of teaching non-violent communication and resolving conflicts; as well as the heritage of world-famous leaders in the struggle for peace. At the same time, «Peace Education» focuses on transforming the methodology, the content of education and pedagogical approaches to combat violence in all its forms. Peace Education involves the study of alternative artistic and narrative teaching methods; democratic methods of partnership pedagogy; inclusive education approaches; as well as the heritage of the leading teachers of the world. The organizational and pedagogical principles of its implementation in the field of higher education, in particular, at UN universities are outlined. The potential of education for peace in the development of transformative education, establishment of social justice and peacebuilding is revealed.